Atypical Radiology Imaging of Squamous Cell Lung Carcinoma: A Case Report and Narrative Review - Nunki Puspita Utomo; Brenda Miriane Rustam; Sudharmadji Sudharmadji (http://dharmais.co.id/, 2023)
Introduction: Multiple well-circumscribed round nodules, also known as “Cannonball” appearance in the lungs, are typically associated with specific pulmonary metastases. However, limited reports denote the finding, especially if correlated with primary squamous cell lung carcinoma in the younger population. This is the first case report in Indonesia of a 19-year-old male with primary squamous cell carcinoma in the lung and chest radiograph image mimicking a “Cannonball” appearance Case Presentation: A 19-year-old male was presented with a history of progressing hemoptysis for two weeks with no other abnormal respiratory symptoms but a reduction of vocal fremitus. The subject is an occasional smoker and had a history of lung tuberculosis in 2009 and a suprarenal or adrenal mass. X-ray imaging revealed multiple bilateral pulmonary nodules, mimicking the “Cannonball” appearance. A fine needle aspiration (FNA) biopsy of a nodule was done and interpreted to be primary squamous cell carcinoma. Symptomatic treatment was given and the subject was discharged on the fifth day. Conclusions: A “Cannonball” appearance or its mimic is not always typical to certain carcinoma based on what this case report finds. In the case of a tumor, radiograph findings should also be correlated with other supporting tests such as biopsy and clinical presentation.